O cacau (Theobroma cacao L.) como substrato na elaboração de bebidas funcionais potencialmente probióticas - Borges, Elder Miguel Esperidião Silva (2021)
Cocoa (Theobroma cacao L.), a fruit of the cocoa tree, is the main ingredient present in the composition of chocolate. However, for its production, the seeds are the only part used, making the pulp of this fruit an agro-industrial residue. Basically, this species can be categorized into three varieties, Forastero, Criollo and Trinitário, each one being responsible for unique characteristics that end up influencing the final product after processing. Many studies have obtained products from this pulp, such as jellies, fine drinks and even ice cream. Based on these applications of cocoa pulp, this study aimed to carry out the physicochemical characterization of cocoa pulp and to evaluate its potential for the production of potentially probiotic beverages. Initially, the characterization of the pulp was carried out through the analysis of pH, titratable acidity (ATT), soluble solids content (SST), reducing sugars (AR) and total reducing sugars (ART). During the analysis, it could be noticed that, with the exception of the soluble solids content, all parameters were within the established by current legislation and in accordance with the data obtained from the literature review. After the literature review and the analysis of the obtained data, it was possible to verify that the cocoa pulp has enormous potential to be applied in processes intended to obtain potentially probiotic beverages. The soluble solids content and the concentration of sugars have the greatest impact on the process of obtaining this drink, considering that they are the most consumed components during the process. After the literature review and the analysis of the obtained data, it was possible to verify that the cocoa pulp has enormous potential to be applied in processes intended to obtain potentially probiotic beverages.